Evaluation of the Application of Accountability Accounting at the Cost Center in the Regional Area of Drinking Water Ake Mayora City of Tidore Islands - Wahyuni; David Saerang; Syermi Mintalangi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Implementation of responsibility accounting is a system to see the responsibilities of each organizational unit based on accountability reports. The aim of this research is to evaluate the implementation of responsibility accounting at the cost center at Perumda Air Minum Ake Mayora, Tidore Islands City. The analytical method used in this research is a qualitative method with a descriptive approach using data from interviews and documentation. The results of this research show that in the implementation of responsibility accounting there are still elements that are not appropriate, namely the classification of controlled and uncontrolled costs has not been made, budget preparation has not been separated according to each section and there is no separation of controlled and uncontrolled costs.